Social Aspects in the Drama Bait Al Asybach (Ian Watt's Sociological Study of Literature) - Syawaluddin, Fauzan Akbar; Komarudin, Edi; Mawardi, Mawardi (Riwayat: Educational Journal of History and Humanities, 2025)
The objective of this study is to reveal the social critique embedded in the drama Bait Al Asybach, focusing on the shifts in moral and spiritual values within society. This drama portrays how cemeteries, which should be sacred and peaceful places, have been neglected by humans who prioritize personal and materialistic interests. The study aims to analyze this phenomenon through a sociological literary approach, specifically Ian Watt's theory. The research employs a qualitative approach utilizing sociological literary theory to analyze the social aspects reflected in the drama Bait Al Asybach. The findings show that Bait Al Asybach critiques materialism, hedonism, and human indifference toward noble values, as illustrated by immoral behaviors occurring in cemeteries. The drama serves as a medium to reflect on social conditions and invites the audience to reconsider the values they uphold in daily life, emphasizing the importance of preserving spiritual values in society.Keywords: Bait Al Asybach; Ian Watt; Sociological Literature